Age at menarche and incidence of diabetes: A prospective study of 300,000 women in China - Yang, L; Li, L; Peters, S; Clarke, R; Guo, Y; Chen, Y; Bian, Z; Yin, J; Tang, Z; Wang, C; Wang, X; Zhang, L; et al. (Oxford University Press, 2017)
Background Previous studies of mostly Western populations have reported inconsistent associations between age at menarche and risk of diabetes. We examined such associations among Chinese adult women who tend to have later menarche age than women in the West. Methods The nationwide China Kadoorie Biobank recruited 302,632 women aged 30-79 (mean 50) years from 10 diverse localities across China in 2004-8 and recorded 5,391 incident cases of diabetes during ~7 years of follow-up. Cox proportional hazards models yielded adjusted hazard ratios (HRs) for incident diabetes associated with age at menarche among those without self-reported or screen-detected diabetes, cancer or CVD at baseline. Results Overall, the mean (SD) age at menarche was 15.4 (1.9) years, although decreasing across successive generations. There was an inverse association between age of menarche and adulthood adiposity. After adjustment for socio-demographic, lifestyle and other reproductive factors, age at menarche was linearly and inversely associated with incident diabetes. The adjusted HRs (95%CI) were 0.96 (0.94-0.97) per 1 year delay of menarche, which was more extreme in younger generations (HRs of 0.93 (0.90-0.97), 0.95 (0.93-0.98) and 0.97 (0.95-0.99) for women born in the 1960s-1970s, 1950s and 1920s-1940s, respectively). After additional adjustment for adiposity, the inverse association completely disappeared in women born in the 1920s-1940s (HR=1.00, 0.97-1.02), but remained significant among women born after the 1950s (HR=0.98, 0.96-1.00). Conclusion In Chinese women age at menarche was inversely associated with incident diabetes. Much of this association was mediated through increased adiposity associated with early menarche, pronounced in older generations.